2015
DOI: 10.5103/kjsb.2015.25.1.085
|View full text |Cite
|
Sign up to set email alerts
|

Influence on the Ground Reaction Force Parameters According to Wearing Positions of Backpacks During Stair Ascending and Descending

Abstract: Purpose : The purpose of this study was to investigate the influence on the ground reaction force parameters according to wearing positions of backpack for during stair ascending and descending.Methods : Participants selected as subject were consisted of young female(n=10) and performed stairs walks(ascending and descending) with 2 types of wearing position(front of trunk [FT], rear of trunk [RT]). Passive(Fz 1) and active(Fz 2) forces of the vertical GRF were determined from time function and frequency domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Patient with CAI have been reported to experience various sports injuries due to ankle instability during landing, which is an essential movement not only in sports situations but also in daily life [42]. To evaluate ankle instability of patients with CAI, GRF was measured using methods such as the gait test, vertical jump, and drop landing [30,31,43]. In the present study, the COP 95% confidence ellipse area was measured during drop landing and it was confirmed that both PEG and SEG significantly decreased the ellipse area compared to NTG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient with CAI have been reported to experience various sports injuries due to ankle instability during landing, which is an essential movement not only in sports situations but also in daily life [42]. To evaluate ankle instability of patients with CAI, GRF was measured using methods such as the gait test, vertical jump, and drop landing [30,31,43]. In the present study, the COP 95% confidence ellipse area was measured during drop landing and it was confirmed that both PEG and SEG significantly decreased the ellipse area compared to NTG.…”
Section: Discussionmentioning
confidence: 99%
“…The variable of the GRF generated based on the time when the affected foot landed on the ground during drop landing was presented at a sampling rate of 2000 Hz. The center of pressure (COP) 95% confidence ellipse area was analyzed by determining the square area created during ground contact when the posture was maintained after landing [31]. Three successful landing motions were recorded, and the most stable motion was selected and used for analysis [32].…”
Section: Ground Reaction Force Measurementmentioning
confidence: 99%
“…The 2nd vertical peak value of active force value is occurred by muscular contraction of near articular system. That is, the 1st vertical value is occurred at 1st touch-down during descending when COG of body transfer to forward-gravity direction, and the 2nd vertical peak value is occurred when COG of body transfer to forward-antigravity direction during ascending (Hyun & Ryew, 2015).…”
Section: Introductionmentioning
confidence: 99%